One- and two-dimensional antenna arrays for microwave wireless power transfer (MWPT) systems and dual-antenna transceivers. Issue 6 (3rd June 2018) - Lin, Yo-Sheng; Hu, Chun-Hao; Chang, Chi-Ho; Tsao, Ping-Chang
ABSTRACT: In this work, we demonstrate novel one-dimensional (1D) and two-dimensional (2D) antenna arrays for both microwave wireless power transfer (MWPT) systems and dual-antenna transceivers. The antenna array can be used as the MWPT receiving antenna of an integrated MWPT and Bluetooth (BLE) communication module (MWPT-BLE module) for smart CNC (computer numerical control) spindle incorporated with the cloud computing system SkyMars. The 2D antenna array has n rows of 1 × m 1D array, and each array is composed of multiple (m) differential feeding antenna elements. Each differential feeding antenna element is a differential feeding structure with a microstrip antenna stripe. The stripe length is shorter than one wavelength to minimise the antenna area and to prevent being excited to a high-order mode. That is, the differential feeding antenna element can suppress the even mode. The mutual coupling between the antenna elements can be suppressed, and the isolation between the receiver and the transmitter can be enhanced. An inclination angle of the main beam aligns with the broadside, and the main beam is further concentrated and shrunk at the elevation direction. Moreover, if more differential feeding antenna elements are used, antenna gain and isolation can be further enhanced. The excellent performance of the proposed antenna arrays indicates that they are suitable for both MWPT systems and dual-antenna transceivers.